Iran’s Surrogate Warfare Strategy against Israel: Geopolitical Maneuvering in the Palestine–Israel Conflict (October 2023–June 2025) - Alwi, Abdullah; Sumadinata, R. Widya Setiabudi; Yulianti, Dina (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
The Israel–Palestine conflict experienced a dramatic escalation following Hamas’s launch of the Al-Aqsa Flood Operation. The conflict triggered broader regional involvement through Iran’s network of allied forces known as the Axis of Resistance. This study analyzes Iran’s surrogate warfare strategy against Israel during the Palestine–Israel conflict from October 2023 to June 2025, focusing on how Iran externalizes the burden of war through proxy forces and technological means. A single-case study design with a qualitative approach was employed. Secondary data include statements from Iranian officials and Axis of Resistance actors obtained through official media channels, reports from think tanks, and international media coverage. Document analysis, content observation, and qualitative content analysis were conducted following Yin, (2018) framework. The study identifies four key dimensions of Iran’s surrogate warfare strategy: (1) delegation and outsourcing to non-state actors, including Hezbollah, Hamas, the Houthi forces, and Iraqi resistance groups; (2) political efficiency achieved through plausible deniability while maintaining strategic influence; (3) multi-level contestation across military, diplomatic, and technological domains; and (4) a strategic shift from indirect confrontation toward a highly limited direct confrontation during the 12-day war in June 2025. Surrogate warfare enabled Iran to project power without direct involvement in the early stages; however, challenges of control and strategic blowback eventually forced limited direct military confrontation with Israel. Iran’s surrogate warfare represents an adaptive response to conventional military asymmetry but faces inherent limitations in controlling autonomous proxy actors and preventing unintended escalation. The transition to direct warfare in June 2025 indicates that surrogate strategies alone cannot address existential security threats, potentially reshaping the dynamics of regional conflict and the future applicability of indirect warfare doctrines.